Objective compressive quantum process tomography - Teo, Y. S.; Struchalin, Gleb; Kovlakov, E.; Ahn, D.; Jeong, Hyunseok; Straupe, S. S.; Kulik, S. P.; Leuchs, Gerd; Sanchez-Soto, L. L. (Physical Review A, 2020)
We present a compressive quantum process tomography scheme that fully characterizes any rank-deficient completely positive process with no spurious a priori information. It uses randomly chosen input states and adaptive output von Neumann measurements. Both entangled and tensor-product configurations are flexibly employable in our scheme, the latter of which are especially compatible with many-body quantum computing. Two main features of this scheme are the certification protocol that verifies whether the accumulated data uniquely characterize the quantum process and a compressive reconstruction method for the output states. We emulate multipartite scenarios with high-order transverse modes and optical fibers to demonstrate that, in terms of measurement resources, our assumption-free compressive strategy can reconstruct quantum processes almost equally efficiently using all types of input states and basis measurements.
CRIS-Team Scopus Importer:2023-04-20